2017
DOI: 10.1021/acsnano.6b07607
|View full text |Cite
|
Sign up to set email alerts
|

Re-Engineering Extracellular Vesicles as Smart Nanoscale Therapeutics

Abstract: In the last decade, extracellular vesicles (EVs) have emerged as a key cell-free strategy for the treatment of a range of pathologies, including cancer, myocardial infarction and inflammatory diseases. Indeed, the field is rapidly transitioning from promising in vitro reports towards in vivo animal models and early clinical studies. These investigations exploit the high physicochemical stability and biocompatibility of EVs, as well as their innate capacity to communicate with cells over long distances via sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
438
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 461 publications
(467 citation statements)
references
References 183 publications
1
438
0
Order By: Relevance
“…It was further suggested that these nano-vesicles with exosome-mimetic properties can be used as a platform for RNAi transfer to the cell cytoplasm (see [127]). However, the high level of cholesterol, ganglioside, and sphingomyelin in exosomal membranes leads to a more rigid bilayer structure than that of their parent cells (see [128]), which suggests that their fusion with lipid-based particles requires rough conditions (see [129]), such as aggressive freeze-thaw processes (see [130]). To avoid the need for such conditions, Yang et al [131] designed a virus-mimetic fusogenic exosome platform to deliver membrane proteins to target cell membranes, involving integrated vascular stomatitis virus G protein, a viral fusogen (see [131]).…”
Section: Extracellular Vesicles (Evs) As a Drug Delivery Systemmentioning
confidence: 99%
“…It was further suggested that these nano-vesicles with exosome-mimetic properties can be used as a platform for RNAi transfer to the cell cytoplasm (see [127]). However, the high level of cholesterol, ganglioside, and sphingomyelin in exosomal membranes leads to a more rigid bilayer structure than that of their parent cells (see [128]), which suggests that their fusion with lipid-based particles requires rough conditions (see [129]), such as aggressive freeze-thaw processes (see [130]). To avoid the need for such conditions, Yang et al [131] designed a virus-mimetic fusogenic exosome platform to deliver membrane proteins to target cell membranes, involving integrated vascular stomatitis virus G protein, a viral fusogen (see [131]).…”
Section: Extracellular Vesicles (Evs) As a Drug Delivery Systemmentioning
confidence: 99%
“…[87] Early reports have linked exosomes, and their miRNA content, with several tissue regeneration processes, such aspects could be soon recapitulated in RM approaches to deliver exogenous miRNA modulators, [88] and their assessment for this purpose has indeed begun to focus on siRNA delivery. [89] Several types of inorganic NPs based on gold, silver, iron, and calcium phosphates (CaP) offer innovative aspects in the journey toward commercially applicable nonviral miRNA delivery vectors. Cysteamine-Au-PEG NPs optimized for miRNA reporters across neuroblastoma and ovarian cancer cell lines built on the beneficial amphipilicity and surface area of these materials.…”
Section: Nonviral Vectorsmentioning
confidence: 99%
“…Compared with monotherapeutic methodology, comprehensive therapy and theranostic nanoplatform based on inorganic functional nanoparticles can overcome the therapeutic dilemmas of multifactorial nature of cancer. So far, substantial efforts have been devoted to design multifunctional MPs DDS, [41][42][43] by directly decorating inorganic nanoparticles on the surface of cell-derived MPs [32,[44][45][46] or previously engineering the parent cells with nanoparticles to obtain MPs with the payloads. [38][39][40] As an excellent drug delivery system, MPs integrated with functional inorganic nanoparticles will provide a new exciting strategy for tumor treatment.…”
Section: Introductionmentioning
confidence: 99%